Comparative metagenomics at Solfatara and Pisciarelli hydrothermal systems in Italy reveal that ecological differences across substrates are not ubiquitous - Ugwuanyi, Ifeoma R.; Fogel, Marilyn L.; Bowden, Roxane; Steele, Andrew; De Natale, Giuseppe; Troise, Claudia; Somma, Renato; Piochi, Monica; Mormone, Angela; Glamoclija, Mihaela (Frontiers in Microbiology, 2023)
Continental hydrothermal systems (CHS) are geochemically complex and support microbial communities that vary across substrates. However, our understanding of these variations across the complete range of substrates in CHS is limited because many previous studies have focused predominantly on aqueous settings. Here we used metagenomes in the context of their environmental chemistry to investigate the ecology of different substrates (i.e., water, mud and fumarolic deposits) from Solfatara and Pisciarelli. Results indicate that both locations are lithologically similar but geochemically distinct. In particular, substrates from Solfatara have similar geochemistry. However, Pisciarelli substrates have varying chemistry; with water and mud from bubbling pools exhibiting high SO42- and NH4+ concentrations. Alpha diversity was different between locations but not across substrates. Over 4000 genera from three kingdoms and viruses were detected in this study using metagenomic profiling which is remarkable for an extremely acidic hydrothermal system. Pisciarelli mud pools, were dominated by hyper(thermophilic) archaea while on average, bacteria dominated Pisciarelli fumarolic deposits and all investigated Solfatara environments. Carbon fixation and sulfur oxidation were the primary metabolic pathways fueled by volcanic outgassing at both locations. Together results demonstrate that ecological differences across substrates are not a widespread phenomenon but specific to the system. Therefore, this study demonstrates the importance of analyzing different substrates of a CHS to understand the full range of microbial ecology to avoid biased ecological assessment.